The impact of short-term changes in sleeping and eating patterns on glucometabolic health and gut microbiota in healthy young adults: a proof-of-concept controlled feeding study - Jiehua Chen; Ruijie Zhang; Chao Zhou; Louise Weiwei Lu; Dana Feng; Haiqiao Zou; Ran Gao; Xinying Zhang; Peiyi Chen; Jiayue Zhu; Haoxie Xu; Nina Zeng; et al. (Food Science and Human Wellness, 2024)
Epidemiological studies showed that night workers are at higher risk of developing chronic metabolic diseases. However, no study has investigated the changes in circadian rhythms caused by a combined effect of sleep and diet in a real-life setting on cardiometabolic health, gut microbiota, and psychological status in healthy people. A 4-week step-wise misaligned-realigned controlled-feeding trial with a 2 × 2 factorial design (sleep and diet) was conducted on healthy young adults. At first, subjects experienced a one-week circadian rhythm misalignment with a high-fat fast-food diet, extended eating window, and delayed sleep schedules, then gradually transited to a complete circadian rhythm realignment with a high-fiber balanced diet, 8-h time-restricted eating, and normal sleep schedules. Circadian rhythm misalignment led to significantly higher levels of fasting glucose and homeostatic model assessment for insulin resistance (HOMA-IR) of subjects compared to baseline and failed to recover to the baseline level in circadian rhythm realignments. Notably, the incremental area under the curve (iAUC) of postprandial glucose decreased with circadian rhythm adjustments as compared to that in circadian rhythm misalignment, suggesting circadian rhythm realignment by sleep or/and diet could partly restore glucose metabolism impaired by a short-term circadian rhythm misalignment. However, circadian rhythm changes did not result in overall perturbations of gut microbiota diversities.